UNIT 3.11 Quantitative Analysis of Surface Expression of Membrane Proteins Using Cold‐Adapted Proteases. Issue 1 (24th September 2013) - Ahmad, Faraz; Kaila, Kai; Blaesse, Peter
Abstract: This unit presents an improved method for quantitative analysis of surface expression of membrane proteins utilizing a cold‐adapted trypsin. Preservation of the proteolytic activity of the enzyme at 0° to 4°C allows cleavage of surface‐expressed membrane proteins at temperatures at which trafficking of the mammalian plasmalemmal proteins is blocked. This provides an important advantage over established trypsin‐cleavage protocols since it can be applied to membrane proteins with a fast turnover rate of the membrane pool and a fast recycling rate. Compared to surface biotinylation, the method is less time consuming. Curr. Protoc. Protein Sci . 73:3.11.1‐3.11.12. © 2013 by JohnWiley & Sons, Inc.